Formation of upper anticyclones and their Blocking activity during winter over Asia - GUPTA , M. G.; RAJAGOPALAN, K. S. V. (MAUSAM, 1970)
The results of the study of 65 cases of the formation of anticyclones in the upper westerlies over Asia and adjoining west Europe, their areas of occurrence and blocking activities, during the winter and transition season of November-April, are presented in this paper. It has also been shown with the help of a detailed case-study of 1-7 April 1969, that the anticyclones which formed over Iran and persisted for more than 5 days behave as blockingsystems and dominate the circulation over Asia. These blocks are however weak when compared with Atlantic and Pacific cases but satisfy all the well known characteristics of blocking action.